Structural behaviour of prefabricated load bearing braced composite timber wall system. (1st December 2018) - Oktavianus, Yusak; Kristombu Baduge, Kasun Shanaka; Orlowski, Kristopher; Mendis, Priyan
Highlights: Five full-scale stiffened oriented strand board (OSB) walls were tested axially. The mid-height lateral deflection may govern the maximum allowable force acting to this wall. Finite element analysis (FEA) results have a good agreement with the experimental work. Combined timber and steel stud may be the best solution to increase both the stiffness and strength of the wall. A potential issue in the construction and the solution has been summarised. Abstract: Timber is gaining its popularity in the construction of low to the mid-rise buildings and sometimes in high-rises due to its sustainability, cost-effectiveness, and availability all around the world. In addition, the prefabricated building is getting popular due to advances in the automation industry, reduction in resources including time, labour, and waste; and cost-effectiveness in mass production. Due to higher capacity demands for mid-rises and convenience in design for manufacturing and assembly (DfMA) in prefabrication, a new development of prefabricated load bearing closed panel composite timber (CPCT) wall system made of oriented strand boards (OSBs) stiffened by sawn-cut timber stud and sometimes with additional steel stud to increase its load carrying capacity has been considered in this research. Five full-scale CPCT walls have been tested subjected to axial compression. The results showed that the mid-height lateral deflection governs the maximum allowable force acting to this wall. Moreover, finite element analysis (FEA) has been done and compared to the experimental results. Once a good agreement between the experimental results and FEA results has been obtained, parametric studies have been performed to comprehensively understand the sensitive parameters affecting the axial behaviour of this system. The parameters studied in this research include the material, the size and the arrangement of the stud, the spacing of the nail, and type of adhesive. Moreover, the possible issue in the practice and the effect of the additional steel stud have also been discussed.